2023
DOI: 10.3390/ma16031014
|View full text |Cite
|
Sign up to set email alerts
|

Novel Photonic Applications of Silicon Carbide

Abstract: Silicon carbide (SiC) is emerging rapidly in novel photonic applications thanks to its unique photonic properties facilitated by the advances of nanotechnologies such as nanofabrication and nanofilm transfer. This review paper will start with the introduction of exceptional optical properties of silicon carbide. Then, a key structure, i.e., silicon carbide on insulator stack (SiCOI), is discussed which lays solid fundament for tight light confinement and strong light-SiC interaction in high quality factor and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 199 publications
0
15
0
Order By: Relevance
“…Most of the magnetometry in SiC is based on DC magnetometry. For DC magnetometry based on ODMR, the most common approach used so far, higher sensitivity can be achieved by simply improving the photon collection efficiency using, for example, waveguides [56,171], nanopillars [172,173] and solid immersion lenses [174,175]. Another approach for increasing the spin read-out contrast for magnetometry in SiC defects could be based on achieving strong coupling by using high-Q macroscopic microwave cavities [176,177].…”
Section: Discussionmentioning
confidence: 99%
“…Most of the magnetometry in SiC is based on DC magnetometry. For DC magnetometry based on ODMR, the most common approach used so far, higher sensitivity can be achieved by simply improving the photon collection efficiency using, for example, waveguides [56,171], nanopillars [172,173] and solid immersion lenses [174,175]. Another approach for increasing the spin read-out contrast for magnetometry in SiC defects could be based on achieving strong coupling by using high-Q macroscopic microwave cavities [176,177].…”
Section: Discussionmentioning
confidence: 99%
“…The films exhibited single crystal orientation (1 0 10), maximum average crystallite size (∼17.7 nm), lowest surface roughness (∼1.10 nm), minimum strain (0.19%), and low dislocation density (∼3.19 × 10 15 ). Similarly, the highest optical and dispersion energy parameters were observed for the samples deposited on Si substrates, including refractive index (η = 2.7707 at λ = 540 nm), bandgap (Eg ∼3.1595 eV), oscillator energy (E o = 7.5980 eV), dispersion energy (E d = 46.1800 eV), dielectric constant (ε ∞ = 7.0779), third order ECS Journal of Solid State Science and Technology, 2024 13 043001 susceptibility (χ (3) ∼ 9.3219 × 10 −12 esu), nonlinear refractive index (η 2 ∼ 2.0793 × 10 −17 m 2 /W), carrier concentration to the effective mass (N/m* = 5.4656 × 10 49 kg −1 cm −3 ), and plasma frequency (ω p = 795.57 cm −1 ). The authors concluded that these findings indicate that films grown on Si are promising candidates for optoelectronics, photonics, and telecommunication applications at elevated temperature and in harsh environments.…”
Section: Summary and Highlights Of Sic X Pvd Techniquesmentioning
confidence: 99%
“…Silicon carbide (SiC x ) thin films, primarily stoichiometric (x ∼ 1) and non-stoichiometric (Si-rich, x < 1 and C-rich, x > 1), continue to be the subject of significant research and development (R&D) and manufacturing initiatives in a continuously growing field of innovative commercial applications. [1][2][3][4][5] The intense R&D and manufacturing interest in SiC x also extends to various forms of the Si-C-N material system.…”
mentioning
confidence: 99%
“…It is also a choice for temperature sensors [ 3 , 4 ]. Meanwhile, SiC also owns many outstanding optical properties, making this material very promising for making photonic and opto-electronic devices [ 5 , 6 , 7 , 8 , 9 ]. SiC has a wide window of transparency, from near ultraviolet to mid-infrared wavelength range, due to the wide bandgap.…”
Section: Introductionmentioning
confidence: 99%